Adsorption of heavy metals cations in wastewater using cement kiln dust - El Zayat, Mohamed Abdel Kareem (AUC Knowledge Fountain, 2015)
Wastewater containing heavy metal constituents are mainly generated from industrial processes, such as electric battery manufacturing, lead smelting and glass industry. Heavy metals are very dangerous and carcinogenic due to the fact that they can bio-accumulate in our bodies resulting in increasing the concentration of chemicals in the biological organism compared to the chemical’s concentration in the environment. A special emphasize in this study is on lead, cadmium, and copper since they are the most common toxic heavy metals in some inorganic industrial wastewater. Common techniques used in heavy metals treatment processes are chemical treatment, flotation, filter coalescence,and membrane filtration. However, they deemed too expensive to meet stringent effluent characteristics. Adsorption process is known with its effectiveness and high efficiency in heavy metals recovery from treated wastewater besides some other physiochemical constituents. Cement Kiln Dust (CKD) as a low cost adsorbent for heavy metal cations uptake was examined for the removal of target heavy metals. Adsorption studies in completely mixed batch reactors were used to generate equilibrium pH adsorption edges. The adsorption behavior of the target heavy metals on the CKD was studied as a function of pH, contact time, sorbent doseand initial metal concentration.Studies showed the ability of CKD to remove the target heavy metals in a pH range below that of precipitation after an equilibrium reaction time of 24 hours maximum. The lead hydroxide precipitation is the dominant phenomenon at pH values > 6.0 while for copper and cadmium, the precipitation started at pH 8.0 to reach approximately 90%. CKD is experimented in dynamic up-flow fixed bed reactors as well using stainless steel columns to study the dynamic breakthrough patterns. Synthetic metal solutes containing the target metals (lead, copper, and cadmium) are fed to the packed columns with the optimum conditionsresulted from the batch equilibrium experiments where the initial metal concentration is 30 mg/l. The experimental runs show that the CKD has a high affinity to adsorb the target metals. The column reactors have higher adsorption capacity than the batch ones for the same initial concentration of adsorbate. The surface concentration at exhaustion in a molar basis was found to be 240 μM/g, 290 μM/g, and 650μM/g for lead, copper and cadmium, respectively. A surface titration experiment indicated negative surface charge of the CKD at pH below 10, meaning that electrostatic attraction of the divalent metals can occur below the pH required for precipitation. However, surface complexation was also important due to the substantive metal removal. Accordingly, a surface complexation model approach that utilizes an electrostatic term in the double layer description was used to estimate equilibrium constants for the protolysis interactions of the CKD surface as well as equilibria between background ions and the sorbent surface. Moreover, the experimental results were fitted to both Langmuir and Freundlich isotherm models to obtain the parameters of each. It was found that the adsorption capacity of CKD had the order Pb≥ Cu>Cd as depicted by Langmuir and Freundlich isotherm models, which is consistent with the electronegativity of these metals;1.854, 1.85, and 1.52, respectively. The sorption capacity at the optimum conditions was 14.85, 14.65, and 14.1 mg/g for lead, copper, and cadmium respectively. The experiments were also supported by Fourier Transform Infra-Red (FTIR) spectroscopy. In addition, scanning electron microscope (SEM) together with energy dispersive X-ray (EDX) were performed to the CKD before and after the treatment process. The SEM and EDX were done using different magnifications in order to better understand the physical and elemental characteristics of CKD before and after adsorption.Hydrated lime as a prime source of CaO, the major constituent of CKD, was also examined at a bench scale as well and compared to CKD in heavy metals uptake. This is to investigate whether the presence of other chemical composition in CKD, such as sodium, chloride, silicon, iron…etc., has any role in the treatment process or not. A pilot scale of a full wastewater treatment plant of 20~25 l/hr capacity was fabricated to investigate the capability of CKD in treating selected industrial wastewater and scaling up of the proposed treatment facility. Raw industrial wastewater from glass manufacturing is introduced to the pilot scale unit. In glass manufacturing, lead oxide, potash, zinc oxide, and other metal oxides are used ascoloring or de-coloring agents. Accordingly, liquid effluents resulted from grinding, polishing, coating and electroplating processes include suspended solids, heavy metals (i.e., lead), and variations in pH. The proposed treatment unit using CKD is able to reduce the total suspended solids (TSS) by 95% and biochemical oxygen demand (BOD) by 72%. In addition, heavy metals concentrations in the raw wastewater, such as lead, copper, chromium, nickel, and zinc, have been effectively treated to meet the international and national permissible limits for restricted irrigation. The highest metal concentration in the examined raw industrial wastewater is lead, and it has been reduced from 31.5 mg/l to 0.242 mg/l. The results were promising and indicated that the introduced methodology can be industrially applied. Finally, the economic viability for the proposed treatment plant was evaluated. The economic indicators in terms of economic rate of return (11.5%) and the positive net economic present value proved that the system is economically and sustainably viable.